PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS PROBLEM BASED LEARNING (PBL) PADA PEMBELAJARAN BAHASA INDONESIA KELAS III SEKOLAH DASAR - Reza Gazali Rahman; Siti Rohana Hariana Intiana; Setiani Novitasari; Hari Witono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to develop student worksheets based on problem based learning in Indonesian language learning for elementary school students that are valid, practical and effective. This study is research and development (R&D) using the 4D model (define, design, develop, and disseminate). The definition stage consists of initial analysis, student analysis, task analysis, concept analysis, and learning objective analysis. The design stage consists of preparing tests, selecting media, selecting formats, and initial design. The development stage consists of expert validation, revision, and limited testing. The deployment stage in this research was not used. Data collection techniques used are tests and questionnaires. The data analysis technique is the analysis of validity, practicality, and effectiveness. Product validity was assessed by two validators with Likert scale analysis. Practicality is determined from the results of teacher and student response questionnaires, and effectiveness is obtained from limited trials to assess N-Gain. The results of the data analysis show that the developed student worksheets: (1) Valid, with an average value of 76.47%, (2) Practically, the average percentage of teacher and student response questionnaires is 77.43%, and (3) Effectively, the average test score before implementing the PBL model was 11.33 and after implementation it was 88.33 then the N-gain test was carried out and an increase of 0.87 was obtained. So it can be concluded that the development of student worksheets based on problem based learning in Indonesian language learning is valid, practical and effective for improving students' abilities.